SAP S/4HANA: Transforming Society with ESG Impact - Pavan Kumar Bollineni (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
SAP S/4HANA represents a transformative force in society through its comprehensive impact on economic, social, and environmental dimensions. This advanced ERP solution enables organizations across diverse sectors to drive operational excellence while simultaneously addressing critical ESG challenges. Through real-time analytics, integrated data management, and process optimization, S/4HANA empowers businesses to enhance productivity, improve social outcomes, and implement sustainable practices. From manufacturing efficiencies to revolutionized healthcare delivery and environmental stewardship, the platform demonstrates how technological innovation can align with broader societal goals. This article explores how S/4HANA serves as a catalyst for ESG initiatives, examining its applications in various industries and its role in creating a more sustainable and equitable future.